Analyzing the impact of various geometries on tri-band antenna performance - Mohd Nor Azami, Mohd Adzimnuddin; Abd Aziz, Mohamad Zoinol Abidin; Ja'afar, Abd Shukur (2023)
A triband antenna that has difference geometry is studied for wireless communication. The study of the transitional structure is studied by maintaining the other design parameter. The simulation of the triband antenna can generate the frequency at 1.73 GHz, 2.33 GHz and 2.74 GHz and have a frequency gap by 400 MHz. Most of the radiation pattern is in bi-directional. The simulated gain is 1.49 dB, 1.25 dB and 0.91 dB respectively.